ALS User Meeting Highlights Accomplishments and Challenges. Issue 1 (2nd January 2016) - Troutman, Keri; Arenholz, Elke; Marchesini, Stefano; Shapiro, David; Zhu, Chenhui; Lanzara, Alessandra; Analytis, James; Vishwanath, Ashvin
Abstract : The 2015 User Meeting brought together 405 ALS users from around the world, many of whom shared insights and sparked discussion with presentations of their ALS research highlights. UEC Chair Chris Cappa launched the meeting with a welcome, followed by another from Berkeley Lab Director Paul Alivisatos. Speaking of the vitality and community that's key to the ALS, Alivisatos also touched on how the ALS could be utilized and optimized with a high-coherence upgrade. ALS Director Roger Falcone outlined short-term and long-term planning for the ALS, with ongoing efforts to develop new beamlines and capabilities within the next three years and beyond.